(untitled) (Research, Society and Development, 2020)
The objective of this work is to show the role of the pharmaceutical professional and Searching for the integrality of health actions and services provided in a health unit also means thinking about the actions and services of Pharmaceutical Assistance, since the pharmacist also participates in the multidisciplinary team from hospital. Considering that the majority of health interventions involve the use of medications and that this use can be decisive for obtaining less or greater results, it is imperative that Pharmaceutical Assistance be seen from a comprehensive perspective, that is, in a much broader way (Duranes, 2017). The methodology used in this study was a literature review on reputable websites. The search for data was carried out in the Literature database, such as the Ministry of Health, SciELO, PubMed, which aimed at gaining knowledge on the subject, including the concept and practices relevant to the exercise of Pharmaceutical Assistance, in addition to verifying the importance of the pharmaceutical professional in promoting of health. The Microsoft Office Word® 2013 program was used to create the flowchart. 33 publications were searched, all publications are in article format, and were found in scientific journals in the areas of public health. In which 18 articles were included, as these were related to the research title and 5 were not included because it was not related to the proposed title.